The presence of tissue renin-angiotensin system components in human burn wounds and scars - Johanneke J. Akershoek; Marcel Vlig; Katrien Brouwer; Wendy Talhout; Robert H.J. Beelen; Esther Middelkoop; Magda M.W. Ulrich (Elsevier, 2018)
Objective: Healing of severe and large surface burn wounds is faced with hurdles such as aberrant wound healing and excessive scar formation. The tissue renin-angiotensin system (tRAS) is involved in dermal wound healing, and fibrosis of other organs. However, little is known about the presence of tRAS during burn wound healing in human skin. This study investigated the presence of tRAS components in human burn wounds and scars. Methods: Dermal tissue biopsies were collected from 39 patients and divided into six categories: burn wounds post burn day (PBD)0-9, PBD11-21 and PBD22-37; young scars (1.5-3.5 months), mature scars (>12 months) and control skin from 9 patients. The tRAS components angiotensin converting enzyme (ACE), chymase, angiotensin receptor 1 (AT1) and Mas receptor were detected via immunohistochemistry. Digital images were acquired and analyzed using image analysis software. Results: Burn wounds from PBD22-37 showed a decreased expression of ACE and chymase compared to earlier time points or control, respectively. In contrast, ACE expression was increased in young scars compared to control skin but was normalized in mature scars. In comparison to control, mature scars showed increased AT1 expression. Conclusions: These results show the presence of components of tRAS in human burn wounds and scars. In addition, they suggest that tRAS has a time-dependent response during burn wound healing. Reduced tRAS might play a role in delayed healing, while an increase during remodeling phase might contribute to scar formation. This research provides a basis for future studies exploring tRAS involvement in burn wounds and scars. Keywords: Tissue renin-angiotensin system, Burn wounds, Scars, Skin